International Comparative Analysis of Time-out Decision Making Strategies Employed by Male University Basketball Coaches: 大學男子籃球隊教練請求暫停考慮因素的跨國比較分析 - CHENG, Warman W. M.; CARRE, Alex F.; KIM, Ku; CARR, Robin (Asian Journal of Physical Education & Recreation, 2003)
LANGUAGE NOTE | Document text in English; abstract also in Chinese. The purpose of this study was to do a comparative analysis of the critical coaching interventions surrounding the use of timeouts employed by male university coaches. Little examination of such game related coaching decision making as a measure of coaching effectiveness has been conducted, particularly at the international level. Fifty-five male coaches of men’s university basketball teams from four different countries (Canada, Hong Kong, South Korea, Taiwan) were analyzed using a questionnaire consisting of demographic questions and a specific six-factor, 26-item timeout questionnaire. Analysis of variance with Scheffe post hoc multiple comparisons was used to examine the results. The findings were: 1. Canadian and South Korean coaches were older and more experienced than coaches from the other countries with Canadian coaches holding more formal certification qualifications. 2. Age, experience and qualifications, however, made no statistically significant difference to the overall results. 3. The "physical" factor was the most common reason for calling timeouts with Hong Kong coaches using this reason most often. 4. The "emotional" factor was the least used reason for calling timeouts for Canadian coaches but was used most often by Korean coaches. 5. Canadian coaches were less likely to use timeouts while Korean coaches were most likely. Canada and Taiwan scored consistently higher than Hong Kong and South Korean coaches and were more similar in their emphasis on all factors. The results suggest a clear difference in the approach to timeout decision making among the coaches from the four countries with the Canadian strategy being consistently different than the other countries of Hong Kong, Taiwan and especially South Korea. The highest emphasis on "physical" factor indicated the importance of using timeouts as a means of controlling team fatigue and energy expenditure. 本研究之目的在於分析大學男子籃球敎練在使用暫停的關鍵抉擇。以往較少研究使用比賽中敎練的決定去分析敎練的敎授成效，本問卷以六種決策方式，分26項來分析四個國家(加拿大、香港、南韓及台灣)的大學男子籃球隊敎練的決策因素，並分析跨國的異同關係。研究指出：一. 加拿大及南韓的敎練年齡較長、經驗較深，而加拿大敎練具有較多正規的証書資格。二. 年齡、經驗及資格與決定因素並無明顯的相關。三. 香港敎練較常以體能因素去請求暫停。四. 加拿大敎練較少以心理因素去請求暫停，而反之南韓敎練則較多。五. 加拿大敎練較少請求暫停而南韓敎練則較多。而在整體因素方面，加拿大及台灣敎練的取向相似並較香港及南韓敎練為高。結果指出加拿大敎練在請求暫停的決定方面與其他國家有明顯的分別，以南韓為甚。體能因素備受重視則引出暫停用作控制球隊疲累及能量消耗問題的重要性。